2013
DOI: 10.1371/journal.pone.0076994
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Profiling in Prostate Cancer - The Diagnostic Potential of Urinary miR-205 and miR-214

Abstract: Prostate cancer (PCa) is the most common type of cancer in men in the United States, which disproportionately affects African American descents. While metastasis is the most common cause of death among PCa patients, no specific markers have been assigned to severity and ethnic biasness of the disease. MicroRNAs represent a promising new class of biomarkers owing to their inherent stability and resilience. In the present study, we investigated potential miRNAs that can be used as biomarkers and/or therapeutic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
121
1
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(130 citation statements)
references
References 80 publications
4
121
1
4
Order By: Relevance
“…Consequently, diagnosing PCOS is dependent on the criteria used [3]. Although PCOS is the most common endocrine disorder in women [2], few susceptibility genes have been repeatedly associated with the syndrome [35]. miRNAs are already being used commercially as disease biomarkers in oncology [17].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, diagnosing PCOS is dependent on the criteria used [3]. Although PCOS is the most common endocrine disorder in women [2], few susceptibility genes have been repeatedly associated with the syndrome [35]. miRNAs are already being used commercially as disease biomarkers in oncology [17].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Carlsson et al [85], evaluating 667 miRNA, found nine miRNAs that consistently differ between malignant prostate tissues and the adjacent normal tissue from each case. Srivastava et al [86] showed that miR-205, miR-214, miR-221 and miR-99b were significantly downregulated in PCa tissues compared to adjacent normal tissue. Areas under the curve (AUCs) obtained by receiver operating characteristics were 0.83, 0.92, 0.75 and 0.86, respectively.…”
Section: Mirna Expression In Pca Tissuementioning
confidence: 99%
“…However, no studies are currently available about miRNAs in urinary exosomes in PCa, even when they have been widely explored in benign nephropathies [119,120]. Table 4 presents published results about miRNAs in urine, showing AUCs between 0.639 and 0.769 [49,86,88,98,[121][122][123][124][125][126][127][128]. Unfortunately, there is not a consensus in miRNAs selected for these studies neither congruence with results published in blood.…”
Section: Mirnas In Urine In Prostate Cancermentioning
confidence: 99%
“…Srivastava et al found low concentrations of miR-205 and miR-214 in the urine samples of 36 prostate cancer patients compared to 12 healthy men (42 ). In a separate study, the role of urinary miR-1825 and miR-484 as diagnostic biomarkers of prostate cancer was analyzed in 8 prostate cancer patients, 12 BPH patients, and 10 healthy controls, as these 2 miRNAs were found to target genes related to prostate cancer development and progression (43 ).…”
Section: Diagnostic and Prognostic Potential Of Circulating Mirnasmentioning
confidence: 99%